The Effect of Replacing Carbohydrate-based Breakfast Foods with Eggs on Cardiometabolic Risk Factors in Adults at Risk for Type 2 Diabetes (P08-045-19). (24th October 2019) - Maki, Kevin; Palacios, Orsolya; Buggia, Mary; Dicklin, Mary; Bell, Marjorie; Maki, Cathleen
Abstract: Objectives: To assess the effect of breakfast egg intake, vs. energy-matched carbohydrate (CHO)-based foods, on insulin sensitivity and markers of cardiometabolic health in adults at-risk for type 2 diabetes. Methods: Overweight or obese adults with prediabetes and/or metabolic syndrome were included in this randomized crossover study consisting of two 4-wk dietary intervention periods, separated by a ≥4 wk washout. During each intervention, subjects consumed study products containing either 2 eggs/d for 6 d/wk (12 eggs/wk) or energy-matched CHO-based foods for breakfast. Percent changes from baseline were assessed for insulin sensitivity; CHO metabolism; lipid metabolism, including lipoprotein lipids, subfactions and particle sizes; high-sensitivity C-reactive protein (hs-CRP); and blood pressures (BP). Results: Overall, 30 subjects (11 male; 19 female) with mean age of 53.5 ± 1.9 y and body mass index (BMI) of 31.9 ± 0.7 kg/m 2 provided evaluable data. Median low-density lipoprotein cholesterol (LDL-C) decreased by 6.0% from a baseline of 119 mg/dL after 4-wk intake of the CHO breakfast foods, which was larger than the 2.9% reduction during the egg condition ( P  = 0.023 between diets). Mean systolic blood pressure was reduced significantly more during the egg condition vs. the CHO condition (2.7% vs. 0.0%, respectively, P  = 0.018) from a baseline value of 127 mmHg. None of the other cardiometabolic risk factor parameters showed significant differences in response between diet conditions. Conclusions: Intake of 12 eggs/wk for breakfast, vs. energy matched CHO-based foods, did not adversely affect the cardiometabolic risk factor profile in men and women at risk for diabetes. Funding Sources: American Egg Board/Egg Nutrition Center, Park Ridge, IL Supporting Tables, Images and/or Graphs